Legal Enforcement of Illegal Bandwidth Reselling in Indonesia: A Friedman Legal System Analysis - Nurfadhilah Nahe; Rusdiyanto Puluhulawa; Irlan Puluhulawa; Manuel Beltrán Genovés (al-Battar: Jurnal Pamungkas Hukum, 2026)
The rapid development of digital transformation has increased the public's need for internet services. However, this increase has not been accompanied by equitable distribution of telecommunications infrastructure, thus encouraging the emergence of illegal bandwidth reselling practices as an alternative to providing internet access. This practice raises various legal issues because it is related to the provision of telecommunications services that require licensing. This study aims to identify and analyze factors that hinder law enforcement against illegal bandwidth reselling practices in Gorontalo Province. The study uses an empirical juridical method by combining a statutory approach, a conceptual approach, and a socio-legal approach. Research data were obtained through interviews with law enforcement officials and a literature review of relevant laws and regulations. Furthermore, all data were analyzed qualitatively using descriptive-analytical methods. The results show that the effectiveness of law enforcement is still hampered by the absence of regulations that explicitly regulate bandwidth reselling practices, weak oversight and coordination mechanisms between institutions, limited capacity of law enforcement officials, and low levels of public compliance with licensing provisions and service agreements. Viewed from the perspective of Islamic Law, this practice is contrary to the principles of al-muslimūna ‘alā syurūṭihim and wafā’ bil ‘uqūd because customers use internet services outside the scope of the agreed contract. This study contributes in the form of an empirical analysis of the relationship between regulatory weaknesses, the capacity of law enforcement officers, and the legal culture of the community in enforcing telecommunications law at the regional level, while also offering recommendations in the form of strengthening regulations, optimizing supervision, and increasing inter-institutional coordination as an effort to increase the effectiveness of law enforcement in the telecommunications sector.